Policies and Strategies of Indonesia in Implementing Regulate to Facilitate to Boost National Digital Economy - Iza, Noor; Marwan, Marwan; Kusumogambriyanto, Kusumogambriyanto (Journal of Law, Politic and Humanities, 2024)
Digital developments must of course be utilized well so that digital economic improvement can be achieved. However, this achievement is certainly not accompanied by the proverbial applause and requires various strategies to achieve it. So, from a national perspective, this research was carried out with the aim of analyzing and expanding Indonesia's strategy in implementing regulations to facilitate the development of the digital economy. The method used in this research is descriptive qualitative with a type of library study so that the data collection technique is carried out by collecting various documents that are related to the research focus. National data that is known to have been collected is then analyzed in depth so that the results of research regarding Indonesia's policies and strategies to facilitate the development of the digital economy are introducing Indonesia's confidence in achieving high targets for e-commerce, developing various strategies that can be used to develop important policies that are in line with dynamic nature of the digital economy, providing education to facilitate the achievement of digital economic strength, providing education and bringing MSMEs to digital platforms, maturing the use of digital payments at every level, building national digital talent, and utilizing community telecommunications network connectivity throughout Indonesia. With this, the national digital economy can improve as envisioned by the Indonesian state.